2017
DOI: 10.1108/ijbm-10-2015-0150
|View full text |Cite
|
Sign up to set email alerts
|

Mobile banking service quality and customer relationships

Abstract: Purpose The purpose of this paper is to investigate the multidimensional concept of mobile banking service quality (security/privacy, practicity, design/aesthetics, enjoyment and sociality) and the impact of the latter on the quality of the relationship (commitment, trust and satisfaction) between consumers and their primary financial institution. Design/methodology/approach An online survey was conducted using a sample of 375 respondents, all owners of a mobile device and all accustomed to conducting bankin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
251
2
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(279 citation statements)
references
References 112 publications
(149 reference statements)
17
251
2
9
Order By: Relevance
“…There are studies conducted which have identified that perception and satisfaction is gender based in case of mobile wallet usage [10] [11]. It has been examined empirically by Arcand et al [12] that dimensions of mobile banking service quality (e.g security/privacy, design/aesthetics, sociality and enjoyment) impacts the relationship quality (e.g. trust, commitment and satisfaction).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are studies conducted which have identified that perception and satisfaction is gender based in case of mobile wallet usage [10] [11]. It has been examined empirically by Arcand et al [12] that dimensions of mobile banking service quality (e.g security/privacy, design/aesthetics, sociality and enjoyment) impacts the relationship quality (e.g. trust, commitment and satisfaction).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The dimension of mobile service quality still be varied. The table 1 represented dimensions of mobile service quality explained by Arcand, PromTep, Brun, and Rajaobelina (2017). Security is no longer an afterthought in anyone's software design and development process rather it is a fundamental dimension for driving Internet banking and mobile banking adoption.…”
Section: Mobile Service Quality (Msq)mentioning
confidence: 99%
“…In the online context, a number of authors have stressed a conceptualization of relationship quality with independent dimensions, considering it to be made up of components of trust, commitment, and satisfaction (Arcand, Promtep, Brun, & Rajaobelina, 2017;Brun et al, 2014;Chung & Shin, 2010;Walsh, Hennig-Thurau, Sassenberg, & Bornemann, 2010). Thus, in the present study, we have conceptualized online relationship quality using three key dimensions of trust, satisfaction, and commitment as related but independent constructs.…”
Section: Relationship Qualitymentioning
confidence: 94%